"It's my soul's responsibility": understanding activists' gendered experiences in anti-fracking grassroots organizations in northern Colorado - Kizewski, Amber Lynn, author; Opsal, Tara, advisor; Shelley, Tara, committee member; Cespedes, Karina, committee member (Colorado State University. Libraries, 2015)
Previous research highlights the relationship between gender and activism in various environmental justice (EJ) grassroots oriented contexts, including but not limited to: the coalfields of Central Appalachia, Three Mile Island, and the Pittston Coal Strike movement. However, little research examining the relationship between gender and activist’s efforts in relation to hydraulic fracturing exists, primarily because this movement itself is relatively new. From 2012-2014, four communities and one county collectively organized in an effort to ban or enact a moratorium on the practice of hydraulic fracturing, commonly referred to as fracking. Anti-fracking activists in Northern Colorado deem this technological advancement as poorly controlled and dangerous to public health and the environment. On the other hand, pro-fracking activists argue that this process is highly engineered, adequately controlled, and necessary to boost and sustain local oil and gas development in Colorado and the United States. Historically, grassroots environmental justice organizations are often created and lead by poor and minority communities as these communities experience the brunt of problematic industry practices. The setting of Northern Colorado is unique in this sense because the communities trying to halt oil and gas development are opposite of what one might expect, as they are predominately white, middle class, and educated. Thus, my study fills current gaps that exist in the literature and adopts an intersectional approach to address the subsequent research question broadly: how do gender, race, and class intersect and impact the nature and extent of activist's efforts in Northern Colorado's Hydraulic Fracturing movement? Ultimately, I find that gendered and raced identities, such as "mother" or "steward to the earth" play an imperative role in explaining women's entry into the fracking movement, while men pull on a spectrum of identities. Furthermore, I find that traditional gendered divisions of labor help to elucidate the differing rates of participation among men and women in the movement, as well as the roles that activists fulfill in grassroots anti-fracking organizations. Ultimately, I argue that exploring gender, in conjunction with race and class on various analytical levels, contributes to a broader understanding of the nuances of activism in environmental justice movements.
It's my soul's responsibility: understanding activists' gendered experiences in anti-fracking grassroots organizations in northern Colorado
Keywords: Colorado; environmental justice; fracking; gender; labor; social movement